UPAYA MENINGKATKAN MINAT BELAJAR PENDIDIKAN AGAMA KRISTEN MELALUI INTEGRASI MEDIA LAGU BERBASIS AYAT ALKITAB DI SD KRISTEN ARASTAMAR BONE KABUPATEN TIMOR TENGAH SELATAN - Ottu, Fransiska (SOSCIED, 2025)
This study aims to analyze the relationship between the implementation of Bible verse songs and the increase in interest in learning Christian Religious Education (PAK) at Arastamar Christian Elementary School in Bone. The research method used is quantitative with a descriptive approach and correlational analysis. The research sample consisted of 32 students, taken from a population of 151 students using a sampling technique based on Suharsimi Arikunto's theory. The validity test results showed that 11 out of 15 statements on the Bible verse song implementation variable (X) and 8 out of 15 statements on the PAK learning interest variable (Y) were valid, with a correlation value ? 0.349. The reliability test showed negative results (-0.38347 for variable X and -3.09991 for variable Y), indicating poor inter-item stability. The normality test using the Liliefors test showed that the data were normally distributed. The hypothesis test indicated a positive and significant relationship between the implementation of Bible verse songs and the increase in interest in learning PAK, with a calculated t-value (68.59531) greater than the t-table value (2.042272) at a significance level of ? = 0.05. However, the correlation coefficient (-0.30641) indicates a weak relationship strength. It can be concluded that the implementation of Bible verse songs has a significant positive effect on increasing interest in learning PAK, although the correlation is weak. This study highlights the potential of song-based approaches to enhance student engagement in learning Christian Religious Education.